O ensino de funções contextualizado à criptografia - Braila, Roberta Maíra Verderi (2021)
The teaching of Mathematics nowadays is facing great difficulties with disinterest of the students in learning the contents, considered for some as a hard job and no return for a future life, as professional though in person, on majority of times they are taught formulas and rules with no explanation of utility of the same subject. Being the functions one of the contents ignored by the students, the objective of this job is to check the student development through a practical application involving Cryptography and functions, bringing subjects of daily, as well as cryptography found in diverse as quite, principally electronics, the classes and the practical utilization differentiated such as game, exercises and computation tools, which culminate a learning of more significant with better performance and a bigger disposition of the students during the classes of this subject.